Dampak Kurs, Suku Bunga, IHSG, Inflasi dan Permintaan Emas Terhadap Harga Emas di Indonesia Tahun 2018-2021 - Lia Sunny Nuraini; Eni Setyowati (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2023)
Gold is a precious metal that is often used as a standard medium of exchange in the finances of various countries and as a medium of exchange in trade. Gold does not face devaluation in price. Gold, a precious metal, is used as currency and medium of exchange in commerce throughout the country. The purpose of this study was to find out how the JCI, inflation, SBI interest rates, and gold demand had an effect on the price of gold in Indonesia during the Covid 19 pandemic. The Least Square Regression Analysis technique is commonly used in this study. OLS). Given the consequences of this exploration and discussion, it can be assumed that gold prices in Indonesia during 2018-2021 will be influenced by Expansion (INF) and Gold Interest (PMEM). Meanwhile, Indonesia's gold price between 2018 and 2021 is not affected by the Rupiah exchange rate against the dollar (KURS), interest rates (BIRATE), or the Composite Stock Price Index (IHSG).